Analysis of Sea Surface Temperature and Chlorophyll-A and Its Relationship with Catch Results Flying Fish Eggs in the Waters of the Kei Islands - Alex S. W Retraubun; Simon Tubalawony; Julius A. N. Masrikat; Ronald Darlly Hukubun (Postgraduate, University of Mataram, 2023)
The Kei Islands water area is quite productive in fisheries management. Environmental characteristics and oceanographic factors in a body of water will determine the potential of fisheries resources in a water body, and influence fish movement patterns and the formation of fishing areas for flying fish eggs. This research aims to examine the distribution of sea surface temperature and chlorophyll-a concentrations and analyze the relationship between sea surface temperature and chlorophyll-a concentrations with catches of flying fish eggs. The research focused on the waters of the Kei Islands, Southeast Maluku, which is an area for catching flying fish eggs. The research data was studied in the period December 2014 â€“ November 2017. SPL and Chlorophyll-a data were downloaded from Citra MODIS-Aqua, while data on flying fish egg production was obtained from PPN Tual. The research results show that the monthly average SST distribution is between 25.03-30.42ÂºC, and the monthly average of chlorophyll-a varies quite widely with a range of 0.05-3.09 mg/m3. The number of flying fish egg production fluctuates every year with a production range of 36.28-81.905 kg. The peak of catching flying fish eggs occurs in June-September (eastern season and transition season II). The results of the analysis show that the correlation between SST and chlorophyll-a variables has a very dominant influence on the abundance of flying fish eggs.